AN ANALYSIS OF MONITORING PRACTICES OF SUPERVISION RESULTS FOLLOW-UP (TLHP) - Fitriani, Nanda Alivia; Wijayanti, Anita (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This research analyzes the flow of TLHP monitoring implementation by APIP based on existing regulations. Then identify the obstacles faced and what policies APIP has implemented in the process of accelerating the completion of audit findings using Edward's Theory of Policy Implementation III. Data and information were obtained by conducting observations, interviews and documentation with two heads of division and two implementing employees at APIP